Traumatic Brain Injury, Current Clinical Management Strategies in ICU: Hands on Manual - Ojum, Sylvanus; Mbaba, Charles; Elem-Ojum, Daniel U (American Journal of Biomedicine and Pharmacy, 2026)
Traumatic brain injury (TBI) is a leading cause of morbidity and mortality, frequently requiring intensive care unit (ICU) management. Current ICU strategies aim to prevent secondary brain injury through early stabilization and continuous neurological monitoring. Initial care focuses on airway protection, adequate ventilation, and hemodynamic stability to ensure sufficient cerebral oxygenation. Intracranial pressure (ICP) monitoring guides targeted interventions to control intracranial hypertension. Maintenance of optimal cerebral perfusion pressure is achieved through fluid management and vasopressor support when necessary. Due to the severity of the social economic health related issue is important to carefully provide veritable guide to doctors especially intensivist on the current protocol from years of experience of different scholars, local and internationally accepted guidelines to serve as a hand on local protocol of management of TBI in the intensive care unit. This manual is based on existing regulatory documents and international accepted method of managing TBI, special and detailed emphases is placed on careful calculation of fluid balance and maximising fluid administration through the enteral route. Overall, ICU management of TBI emphasizes multidisciplinary, protocol-driven care to improve neurological outcomes.